Determining sustainable lignocellulosic bioenergy systems in the Cape Winelands District Municipality, South Africa - Von Doderer, Clemens Cornelius Christian (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD(Agric))--Stellenbosch University, 2012.